2007
DOI: 10.1080/10715760601064714
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ozone-induced SP-A oxidation by plant polyphenols

Abstract: Surfactant protein-A (SP-A) is the best studied and most abundant of the protein components of lung surfactant and plays an important role in host defense of the lung. It has been shown that ozone-induced oxidation of SP-A protein changes its functional and biochemical properties. In the present study, eight plant polyphenols (three flavonoids, three hydroxycinnamic acids, and two hydroxybenzoic acids) known as strong antioxidants, were tested for their ability to inhibit ozone-induced SP-A oxidation as a mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
1
6
0
1
Order By: Relevance
“…We speculate that this increase occurs because of the lack of SP-A, an important host defense protein that plays an antioxidant or oxidant scavenger role in the alveolus. This is based on several converging lines of evidence including: 1) the attribution of an antioxidant role to SP-A [101][102][103]; 2) the demonstration that SP-A is highly susceptible to oxidative modification by carbonylation) [53] and to ozone-induced oxidation of methionine residues [34], and that its function is disrupted by these oxidative modifications) [9,[31][32][33][34]; and 3) the description of other systems in which proteins serve as "sacrificial antioxidants" [104][105][106][107][108][109].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We speculate that this increase occurs because of the lack of SP-A, an important host defense protein that plays an antioxidant or oxidant scavenger role in the alveolus. This is based on several converging lines of evidence including: 1) the attribution of an antioxidant role to SP-A [101][102][103]; 2) the demonstration that SP-A is highly susceptible to oxidative modification by carbonylation) [53] and to ozone-induced oxidation of methionine residues [34], and that its function is disrupted by these oxidative modifications) [9,[31][32][33][34]; and 3) the description of other systems in which proteins serve as "sacrificial antioxidants" [104][105][106][107][108][109].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the changes in WTO 3 mice are likely due to oxidative stress resulting from acute ozone exposure. We have demonstrated that SP-A is highly susceptible to oxidative modification and that its modification significantly compromises its function)) [31][32][33]53,[115][116][117]. In WT mice SP-A is an abundant BAL protein and several lines of evidence have linked it to redox regulation and led investigators to propose an antioxidant function for SP-A.…”
Section: Comparison Of Wt and Ko Micementioning
confidence: 97%
See 1 more Smart Citation
“…High levels of ROS react with cellular components including DNA, proteins, and lipids leading to cellular and tissue damage [278]. Resveratrol and other dietary stilbenes reduce oxidative stress by acting either as a direct scavenger of ROS [279] or as an inhibitor of NADPH oxidase expression and xanthine oxidase activity [280]. Resveratrol has low toxicity [281].…”
Section: Approachesmentioning
confidence: 99%
“…However, the precise mechanisms by which SP-A protects the lungs from oxidant-induced cellular injury remain unclear. Interestingly, we now recognize that in addition to the protective effects of SP-A against oxidant-induced cellular damage, the function of SP-A itself can be impaired by oxidation 9193 . Inhalation of ozone impairs the functional interaction between SP-A and either lung macrophages or alveolar epithelia 9495 .…”
Section: Genes Of Innate Immunity and Ambient Ozonementioning
confidence: 99%